A Semiotic Study of Communication in the Chant 'Pokoknya NW, Pokok NW, Iman dan Takwa' as an Educational Medium - Ibrahim, M.; Naami, Nazar; Thohri, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
The chant 'Pokoknya NW, Pokok NW, Iman dan Takwa' is a significant medium used in educational contexts to promote religious and moral values. This study explores the semiotic aspects of the chant to understand its role and effectiveness in communication and education. The research aims to analyze the symbols and meanings embedded in the chant, and how they contribute to the construction of collective identity and educational outcomes. A qualitative research methodology was employed, utilizing semiotic analysis to decode the signs and symbols present in the chant. Data collection techniques included document analysis and interviews with educators and students who frequently use the chant. Data were analyzed using Peirce's triadic model of semiotics, focusing on the relationship between the sign, its object, and its interpretant. The findings reveal that the chant 'Pokoknya NW, Pokok NW, Iman dan Takwa' effectively conveys core values of faith and devotion, serving as a powerful tool for character education. The repetition and rhythm of the chant enhance memory retention and group cohesion, reinforcing shared values and beliefs. Additionally, the study identifies the chant's role in fostering a sense of belonging and identity among participants. The implications of this research highlight the importance of integrating semiotic analysis in educational practices to better understand and utilize cultural artifacts like chants in promoting educational goals. By recognizing the semiotic richness of such chants, educators can enhance their pedagogical strategies to foster moral and religious education more effectively.